As chaves para o mundo do quinto império: as imagens de mundo na história do futuro do padre Antonio Vieira - Macedo, Gil Eduardo de Albuquerque (2014)
Iconic historical figure, Antônio Vieira (1608-1697) is regarded as an essential character to the Luso-Brazilian history. Between 1646 and 1667, the priest began writing the History of the Future, the first volume of the celebrated "Clavis Prophetarum , political and theological unity that would leverage the process of spread of Christianity across the globe, recognizing Portugal as forefront and center of all millenarian movement. Them, Jesuit represented the "World" in two metaphors: "theater" and "body" responsible for viewing spaces of abstract Christian truth. Starting from the hermeneutical assumptions of analysis, we investigated the historical relations present in the construction of such representations, by which establish the dialogue between politics, theology and seventeenth-century rhetoric. Therefore, the following study supports the hypothesis that beyond a mere stylistic expressions, spatial metaphors of "World" were formulated by Antonio Vieira as a resource that could sharpen the minds of his readers, engaging words into action, become alive and effective use of rhetoric